2010
DOI: 10.1038/sj.bjc.6605586
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of HER2-positive metastatic breast cancer with lapatinib and capecitabine in the lapatinib expanded access programme, including efficacy in brain metastases – the UK experience

Abstract: BACKGROUND:The global lapatinib expanded access programme provided access to lapatinib combined with capecitabine for women with HER2-positive metastatic breast cancer (MBC) who previously received anthracycline, taxane and trastuzumab. METHODS: Progression-free survival (PFS) and safety data for 356 patients recruited from the United Kingdom are reported. Efficacy was assessed in 162 patients from the five lead centres, including objective tumour response rate (ORR), time to disease progression (TTP) and effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(76 citation statements)
references
References 14 publications
4
69
0
3
Order By: Relevance
“…Our retrospective evaluation of safety and efficacy of LC in this population with BMs showed a 27.1% ORR similar to previous experience in the literature [12][13][14][15][16][17]. Moreover, survival outcomes including PFS of 7monthsandOSof13monthsweresimilartotheliterature confirming the efficacy of LC in BMs of HER2+ MBC patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our retrospective evaluation of safety and efficacy of LC in this population with BMs showed a 27.1% ORR similar to previous experience in the literature [12][13][14][15][16][17]. Moreover, survival outcomes including PFS of 7monthsandOSof13monthsweresimilartotheliterature confirming the efficacy of LC in BMs of HER2+ MBC patients.…”
Section: Discussionsupporting
confidence: 87%
“…However, it remains unansweredwhetherthehighfrequencyofBMsismerelyrelatedtotheaggressivenessofHER2+disease.Nevertheless, theobservationisveryrelevant,andnovelagentsmoreefficientatpenetratingtheCNStopreventortreatCNSmetastasesareurgentlyneeded.Ithasbeensuggestedthatlapatinib maydecreasetheriskofdevelopingCNSmetastases.InapreclinicalstudybyPalmierietal. [18],lapatinibwasreportedto inhibittheformationofmetastasesinHER2+humanbreast carcinomacells.Inaccordancewiththisobservation,several studies have reported efficacy of LC combination treatment inthispatientpopulation [13][14][15][16][17]. In a phase III study evaluating capecitabine versus LC therapyinMBCpatients,theadditionoflapatinibwasshown tobeassociatedwithareducedincidenceofBMsasthefirst site of relapse, which has been considered as a preventive effect [9,11].…”
Section: Discussionmentioning
confidence: 85%
“…2,3 In addition, it showed interesting activity in patients with brain metastasis. [4][5][6][7] Skin rash, diarrhea, and hepatic toxicities are adverse events (AEs) that have been linked with not only lapatinib, [8][9][10][11] but also other EGFR TKIs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we were constrained to use contrast-enhanced images for efficacy assessment instead of T2/FLAIRE images. Second, in recent medical literature, volumetric response criteria and RECIST have been used as primary endpoints to evaluate agents in brain metastasis breast cancer patients (7,(24)(25)(26). Because this was a single-arm study, it was critical to use similar assessment criteria to be able to compare with previous study results.…”
Section: Discussionmentioning
confidence: 99%